Examing the relationship between website visits and purchase intentions for internet shoppers: implications for international marketers. (1st November 2007) - MacDonald, Jason; Elahee, Mohammad Niamat
This paper examines possible determinants of the frequency with which consumers visit websites for high-involvement products. A path model of website visit frequency is tested using Amos 4.0. The main predictors in the model were purchase intentions and social motives. Social motives refer to desires to gather pertinent information about a product that will enable the browser to socialise with others. Analyses of the results suggest that social motives have a greater affect than purchase intentions on the frequency with which consumers visit websites.